Plant resistance to leaves and their effects on paddy rice production in Kutai Barat District, East Kalimantan Province, Indonesia - Akhsan, Ni'matuljannah; SOPIALENA; FAHRIZAL (Asian Journal of Agriculture, 2019)
Abstract. Akhsan N, Sopialena, Fahrizal. 2019. Plant resistance to leaves and their effects on paddy rice production in Kutai Barat District, East Kalimantan Province, Indonesia. Asian J Agric 3: 41-46. This study was aimed to evaluate the effect of fertilizer application on the resistance of lowland commercial rice cultivars (Oryza sativa L.) against leaf spot diseases in Kutai Barat District, East Kalimantan Timur, Indonesia and to determine the factors influencing the resistance. A field experiment was conducted at rice fields in Long Iram and Linggang Bigung Sub-districts, West Kutai District and the disease identification was performed at the Laboratory of Pests and Diseases, Faculty of Agriculture, Mulawarman University. The field experiment was designed in a split-plot design arranged in a Randomized Block Design (RBD) using four replications. The main-plot was fertilizer application (P) consisting of two fertilizer application treatments, i.e., 200 kg.ha-1 Urea (p1), and 200 kg.ha-1 Urea + 200 kg.ha-1 NPK (p2). The sub-plots were varieties (V) consisted of three varieties, i.e., Ciherang (v1), Mekongga (v2) and Inpari 6 (v3). The disease identification was performed by identification of leaf spot disease isolated from the sample plants using morphological observation under a microscope. The number and density of stomata, intensity of leaf disease infection, and yield of the rice were observed. The humidity was also measured at the time of observation of leaf spot disease intensity. The results showed that different fertilizer treatments did not affect the leaf spot disease intensity but the varieties affected the disease intensity at 7, 14, 21.35 and 49 days after planting. The number of stomata of Ciherang, Mekongga and Inpari 6 varieties was 230,182 and 236 stomata/mm2, respectively. Ciherang variety was more resistant against the leaf spot disease compared to other varieties. Stomatal density does not always affect the intensity of leaf spot disease in lowland rice. There is a correlation between air humidity and the intensity of leaf disease infection. The interaction between fertilization and varieties was significant for the rice yield and the highest yield was obtained by Ciherang variety fertilized with 200 kg.ha-1 Urea + 200 kg ha-1 NPK about 3.58 Mg.ha-1 (grain wet weight).In conclusion, Fertilizer application does not affect the leaf spot disease infection and Ciherang variety is the most resistant plant against leaf spot disease compared to Mekongga and Impari 6 varieties.